POTENSI PARASITOID TELUR PENGGEREK BATANG PADI KUNING Scirpophaga incertulas Walker PADA BEBERAPA TIPOLOGI LAHAN DI PROVINSI JAMBI - . Wilyus; Fuad Nurdiansyah; Siti Herlinda; Chandra Irsan; Yulia Pujiastuti (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2012)
The research was conducted to analyze the diversity, dispersal and domination of the egg parasitoid species of the yellow rice stem borer Scirpophaga incertulas Walker on several land typologies in Jambi Province. The study was conducted by survey method, from December 2010 until June 2011. Samples of egg parasitoids of S. incertulas were collected by baiting parasitoids with eggs of S. incertulas. The results of the research showed that there were three spesies of the egg parasitoids of S. incertulas found in Jambi Province, the most dominant was Telenomus rowani Gahan, followed by Trichogramma japonicum Ashmead and Tetrastichus schoenobii Ferriere. T. rowani and T. japonicum were found in all wetland ecosystems in Jambi Province (tidal swamp, swampy area, rainfed lowland, lowland technical irrigation, and upland technical irrigation), while T. schoenobii was found only in tidal swamp, swampy area, and lowland technical irrigation. The highest species diversity of egg parasitoid of S. incertulas was found on tidal swamp (Shannon index 1.047), followed by swampy area, lowland technical irrigation, rainfed and upland technical irrigation area. The average of proportion of egg masses parasitized by T. rowani, T. japonicum and T. Schoenobii were 22.58, 6.18 and 2.68% respectively. The average of individual eggs parasitized by T. rowani, T. schoenobii, and T. japnicum were 8.41, 1.67 and 1.47% respectively.